Relevance of Bhartrihari’s Vakyapadiya in the Digital Age - Tripathi, Pooja (Bodhi: An Interdisciplinary Journal, 2024)
In the digital age, where media are diverse and constantly evolving, Bhartrihari’s ancient text, the Vakyapadiya, remains profoundly relevant. This paper highlights how Bhartrihari’s insights into language and meaning can be applied to modern digital communication, which often involves emojis, slang, and varying contexts. The study emphasizes the importance of Bhartrihari’s concept of Apabhramsa, which helps in interpreting new language by relating it to familiar terms. Additionally, the paper explores how the Vakyapadiya’s ideas about words representing both general concepts and specific instances are crucial for understanding the wide range of digital content. Bhartrihari’s notion that a single word can have multiple meanings is also examined for its role in accurate digital interpretation. Through this exploration, the research demonstrates how Bhartrihari’s principles can offer valuable insights into effective communication and inclusivity in today’s interconnected digital world.